2020
DOI: 10.31219/osf.io/rtfkw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pushing the (Visual) Narrative: the Effects of Prior Knowledge Elicitation in Provocative Topics

Abstract: Narrative visualization is a popular style of data-driven storytelling. Authors use this medium to engage viewers with complex and sometimes controversial issues. A challenge for authors is to not only deliver new information, but to also overcome people’s biases and misconceptions. We study how people adjust their attitudes toward (or away from) a message experienced through a narrative visualization. In a mixed-methods analysis, we investigate whether eliciting participants’ prior beliefs, and visualizing th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…A first study investigating persuasive data videos indicated that such videos have the potential to influence peoples’ attitude [CSF*19]. Heyer et al [HRR20] found that the elicitation and incorporation of participants’ prior knowledge in a visual narrative does not lead to a significant effect on attitude change. However, they showed that visualizations are generally more persuasive compared to textual representations.…”
Section: Background and Related Workmentioning
confidence: 99%
“…A first study investigating persuasive data videos indicated that such videos have the potential to influence peoples’ attitude [CSF*19]. Heyer et al [HRR20] found that the elicitation and incorporation of participants’ prior knowledge in a visual narrative does not lead to a significant effect on attitude change. However, they showed that visualizations are generally more persuasive compared to textual representations.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Heyer et al [15] investigated how eliciting prior knowledge, particularly knowledge around provocative topics, could influence misconceptions in visualization. They conducted an experiment that found that visualization was more persuasive than just text, but that eliciting prior knowledge did not affect persuasiveness.…”
Section: Believabilitymentioning
confidence: 99%
“…An analyst elicits knowledge that is valuable to the organization from an expert [Wat85]. Some work similarly exists examining attitude elicitation, e.g., to assess its impact on provocative topics [HRR20].…”
Section: Belief Knowledge Preference and Attitude Elicitationmentioning
confidence: 99%